Performing European Memories - Gluhovic, Milija. author. aut Link
XII, 334 p.
Keywords: Asking whether a genuinely shared European memory is possible while addressing the dangers of a single, homogenized European memory, Gluhovic examines the contradictions, specificities, continuities and discontinuities in the European shared and unshared pasts as represented in the works of Pinter, Tadeusz Kantor, Heiner Muller and Artur Zmijewski.